„die ganze Mensch‑ und Tiergemeinschaft überblicken“ – literarische Grenzverhandlungen des Humanen bei Franz Kafka - Sommerfeld, Beate (Uniwersytet Gdański, 2019)
Kafkas hybride Tierfiguren stehen in einer höchst vielschichtigen Gemengelage von zeitgenössischen Debatten und Diskursen Sie werden jeweils mittels spezifisch literarischer Darstellungsformen verarbei‑ tet In der dekonstruktiven Verunsicherung der Mensch‑Tier‑Grenze und der Schaffung von Schwellen‑ räumen machen Kafkas Texte Anleihen bei der Romantik Der Beitrag fokussiert insbesondere Kafkas kreative Umschriften phantastischen Erzählens und romantischer Ironie.

Kafka’s hybrid animal figures are situated in a complex set of contemporary debates and discourses always modified through specific literary presentation forms In the deconstructive questioning of the human‑animal frontier and the creation of threshold spaces, Kafka’s texts refer to the Romantic tradition In particular, the article focuses on Kafka’s creative transcriptions of fantastic narration and romantic irony.
“To survey the whole human and animal community” – literary negotiations of the human‑animal border in the work of Franz Kafka
Keywords: Franz Kafka, Tierfiguren, cultural animal studies, Romantik, Hybride; Franz Kafka, animals, cultural animal studies, Romanticism, hybrids